Clinical Image-Based Procedures. Translational Research in Medical Imaging: 4th International Workshop, CLIP 2015, Held in Conjunction with MICCAI 2015, Munich, Germany, October 5, 2015. Revised Selected Papers - Oyarzun Laura, Cristina; Shekhar, Raj; Wesarg, Stefan; González Ballester, Miguel Ángel; Drechsler, Klaus; Sato, Yoshinobu; Erdt, Marius; Linguraru, Marius George (Lecture Notes in Computer Science, 2016)
This bookconstitutes revised selected papers from the 4th International Workshop onClinical Image-Based Procedures, CLIP 2015, held in conjunction with MICCAI2015 in Munich, Germany, in October 2015. The 15 papers presented in thisvolume were carefully reviewed and selected from 22 submissions. CLIPfocuses on translational research; therefore, the goal of the works presentedin this workshop is to bring basic research methods closer to the clinicalpractice. A highlight of this workshop is the subject of strategies forpersonalized medicine to enhance diagnosis, treatment and interventions.